Republic of Tajikistan : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Tajikistan. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Republic of Tajikistan's Request for Disbursement Under the Rapid Credit Facility (RCF). The coronavirus disease 2019 (COVID-19) pandemic has had a severe human and economic impact in Tajikistan. Trade and transportation disruptions have led to a sharp drop in remittances and government revenues and created urgent balance of payments and fiscal financing needs. The authorities have responded with an action plan and measures to contain the pandemic. Health spending and targeted support to the most vulnerable households and sectors in the economy are the immediate priorities, and a temporary widening of the budget deficit is appropriate. The IMF's financial assistance under the RCF is expected to provide a sizable share of the financing needed to implement the anti-crisis measures. Additional concessional and grant financing from the international community will be critical to close the remaining financing gap. Based on authorities' fiscal consolidation plans, debt is assessed to be sustainable. The authorities have committed to enhance the transparency and governance of their COVID-19 policy response through the publication of an ex-post audit of associated spending and procurement processes. The risk of debt distress remains high, but the capacity to repay the IMF is adequate.